Trafficking Dalam Hadis dan Perkembangannya Dalam Konteks Kekinian - Suryadilaga, Muhammad Alfatih (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
Trafficking in women and children is a form of slavery. Legal laws highly respect human rights and clearly prohibit human trafficking. This trafficking, nevertheless, is mushrooming nowadays, and is like a chain that has no edge. Islam, which comes as a mercy for all, fully appreciates children's and women's rights. Historically, the coming of Islam has elevated the status of women. The Prophet Muhammad was a hero in combating woman trafficking, as it brought about sexual exploitation and prostitution. Trafficking places women as its object and, therefore, the modem society has to leave it. On top of that, the Qur'an and Hadith definitely ban it